Of Necessity: Making Decisions About Our Daughter’s Early Learning Years (LEARNing Landscapes, 2012)
Parents play significant roles in their children’s learning. Part of those roles include making decisions about when and where their children go to school, or, if those decisions are, or seem, impossible, parents make decisions about how they are going to navigate this apparently inevitable relationship—parents and schools. This article explores some decisions two parents made about their daughter’s learning as she headed into school, and during her early school years. The author is aware that not all parents would, or even could, make some of the decisions he made with his partner about their child’s learning. The stories contained in this article are offered not as examples of what constitutes good parenting, or good decision-making about relationships with schools, but as reflective pathways into understanding how difference locates us within expected relationships.
Keywords: Parents; learning; school; decision making